Extraction of second harmonic from an InP based planar Gunn diode using diamond resonator for milli-metric wave frequencies. (February 2016) - Maricar, Mohamed Ismaeel; Khalid, Ata; Cumming, D.R.S.; Oxley, C.H.
Highlights: InGaAs planar Gunn diode with on chip matching circuit. Circuits to extract second harmonic for milli metric and terahertz frequencies. Novel diamond shaped resonator to suppress the fundamental and extract the harmonic. Highest recorded experimental power at the second harmonic from a planar Gunn diode. Abstract: Planar Indium Gallium Arsenide (In0.57 Ga0.47 As) Gunn diode was fabricated on a semi-insulating indium phosphide substrate with on chip matching circuit to enable the extraction of second harmonic in millimeter and terahertz frequencies. The In0.57 Ga0.47 As planar Gunn diodes were designed with an active length of 4 μm, channel width of 120 μm and integrated with a novel diamond resonator to suppress the fundamental and extract the second harmonic. The experimental results gave good fundamental suppression and extraction of second harmonic (121.68 GHz) with an RF output power of −14.1 dBm. This is highest recorded power at the second harmonic from a planar Gunn diode.